2019
DOI: 10.1246/bcsj.20190260
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A New Heterometallic MOF in Cyanosilylation Reaction, Treatment and Care Management Value in Stroke by Reducing Oxidative Stress Damage

Abstract: By employment the heterometallic strategy, a new highly porous metal-organic framework {(Me2NH2)[Mn3K2(TZIA)3(H2O)3]·(DMF)4}n (1) was prepared via corresponding K(I)and Mn(II) salts and hetero-donor organic ligand 5-(1H-tetrazol-5-yl)isophthalic acid (H3TZIA) via solvothermal conditions in water and DMF mixed solvent. X-ray study of a single crystal shows that ionic K+ was immobilized on the surface of pores via trinuclear Mn2+–tetrazole coordination motif. The resulting activated 1a has been explored in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[5][6][7] Therefore, a controlled ROS prevention may reduce the incidence of the ROS-involved diseases. [8][9][10] Nevertheless, ROS is a double-edge sword; cellular production of ROS plays a very significant positive role in physiological responses in a number of cases including cell redox signaling, cell homeostasis, and cellular apoptosis (programmed cell death), 2,[11][12][13] where induction of cellular apoptosis in cancer cells has become a conventional strategy in nanomedicine for cancer therapy.…”
Section: (Break)mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Therefore, a controlled ROS prevention may reduce the incidence of the ROS-involved diseases. [8][9][10] Nevertheless, ROS is a double-edge sword; cellular production of ROS plays a very significant positive role in physiological responses in a number of cases including cell redox signaling, cell homeostasis, and cellular apoptosis (programmed cell death), 2,[11][12][13] where induction of cellular apoptosis in cancer cells has become a conventional strategy in nanomedicine for cancer therapy.…”
Section: (Break)mentioning
confidence: 99%
“…Excessive ROS that cannot be eliminated by the biological antioxidant system will lead to oxidative stress damage to all cell components, including protein oxidation, lipid peroxidation, and DNA damage. It has been revealed that oxidative stress is involved in many human diseases, including Alzheimer’s disease, Parkinson’s disease, strokes, diabetes, inflammation disorders, cancer, and so on. Therefore, a controlled ROS prevention may reduce the incidence of the ROS-involved diseases. Nevertheless, ROS is a double-edge sword; cellular production of ROS plays a very significant positive role in physiological responses in a number of cases including cell redox signaling, cell homeostasis, and cellular apoptosis (programmed cell death), , where induction of cellular apoptosis in cancer cells has become a conventional strategy in nanomedicine for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%